Integrability analysis of regular and fractional Blackmore-Samulyak-Rosato fields - Blackmore, D.; Urban, K.; Rosato, A. (Condensed Matter Physics, 2010)
Blackmore-Samulyak-Rosato (BSR) fields, originally developed as a means of obtaining reliable continuum approximations for granular flow dynamics in terms of relatively simple integro-differential equations, can be used to model a wide range of physical phenomena. Owing to results obtained for one-dimensional granular flow configurations, it has been conjectured that BSR models of fields with perfectly elastic interactions are completely integrable infinite-dimensional Hamiltonian systems. This conjecture is proved for BSR models in one space dimension, and analogues of BSR fields involving fractional time derivatives are briefly investigated. Установлено, що BSR поля, початково розвинені як засіб одержання надійних континуумних апроксимацій для динаміки гранулярних потоків на мові відносно простих інтегро-диференціальних рівнянь, можна використовувати для моделювання широкого спектра фізичних явищ. Завдяки результатам, одержаним для конфігурацій одновимірного гранулярного потоку, зроблено припущення, що BSR моделі полів із ідеально пружними взаємодіями є повністю інтегровними нескінченновимірними гамільтоновими системами. Це припущення доведено для BSR моделей в одновимірному просторі, і аналоги BSR полів, що включають часткові похідні за часом, досліджені стисло.